The isomiR-140-3p-regulated mevalonic acid pathway as a potential target for prevention of triple negative breast cancer - Anjana Bhardwaj; Harpreet Singh; Celestine Marie Trinidad; Constance T. Albarracin; Kelly K. Hunt; Isabelle Bedrosian (Breast Cancer Research, 2018)
Abstract Background Prevention of triple-negative breast cancer (TNBC) is hampered by lack of knowledge about the drivers of tumorigenesis. Methods To identify molecular markers and their downstream networks that can potentially be targeted for TNBC prevention, we analyzed small RNA and RNA sequencing of a cell line model that represent early stages of TNBC development. We have identified direct gene targets of isomiRNA-140-3p and by using cell-based and in vivo model systems we have demonstrated the utility of targeting downstream pathways for prevention of TNBC. Results These analyses showed that 5’isomiRNA of miR-140-3p (miR-140-3p-1) and its novel direct gene targets, HMG-CoA reductase (HMGCR) and HMG-CoA synthase 1(HMGCS1), key enzymes in the cholesterol biosynthesis pathway, were deregulated in the normal-to-preneoplastic transition. Upregulation in the cholesterol pathway creates metabolic vulnerability that can be targeted. Consistent with this hypothesis, we found direct targeting of miR-140-3p-1 and its downstream pathway by fluvastatin to inhibit growth of these preneoplastic MCF10.AT1 cells. However, although, fluvastatin inhibited the growth of MCF10.AT1-derived xenografts, histological progression remained unchanged. The cholesterol pathway is highly regulated, and HMGCR enzymatic activity inhibition is known to trigger a feedback response leading to restoration of the pathway. Indeed, we found fluvastatin-induced HMGCR transcript levels to be directly correlated with the degree of histological progression of lesions, indicating that the extent of cholesterol pathway suppression directly correlates with abrogation of the tumorigenic process. To block the HMGCR feedback response to statins, we treated resistant preneoplastic cells with an activator of AMP-activated protein kinase (AMPK), a brake in the cholesterol feedback pathway. AMPK activation by aspirin and metformin effectively abrogated the statin-induced aberrant upregulation of HMGCR and sensitized these resistant cells to fluvastatin. Conclusions These results suggest the potential use of combined treatment with statin and aspirin for prevention of TNBC.